Creation of and measurement of low adhesion conditions for the development of on-train low adhesion detection equipment - Tim Harrison; Bilal Abduraxman; Peter Hubbard; Christopher Ward; B. White; D. Fletcher; K. Chandrasekhar; R. Lewis; D. Vincent; S. Chaney; M. Burstow; E. Cockcroft (2024)
Low adhesion conditions have a significant effect on the operation of rail networks. Each Autumn in the UK, leaf fall timetables are introduced, adjusting timings so that drivers can adopt more defensive driving techniques. A rail system’s situational awareness would be greatly increased if each train could report the adhesion conditions for the track over which it had just passed, allowing optimised operation of both service trains and rail head treatment trains. The testing presented here was commissioned to provide data for the development of an on-train Low Adhesion estimation system that can estimate the adhesion conditions beneath a rail vehicle in near real-time. This paper describes the instrumentation and testing of a full-scale vehicle over a section of track with artificially lowered adhesion conditions. The dynamic properties of the vehicle are shown to change with adhesion level.